The Effect of Earnings Aggressiveness and Income Smoothing on Firm Value with Good Corporategovernance as a Moderating Variable in Pharmaceutical Companieson The Indonesia Stock Exchange - David Yanto Daniel Mahulae (Institute of Computer Science (IOCS), 2021)
Earnings Aggressiveness and Income Smoothing on the Value of Pharmaceutical Companies on the Indonesia Stock Exchange (2) analyzes whether Good Corporate Governance can be a moderating variable of the effect of Earnings Aggressiveness and Income Smoothing on the Value of Pharmaceutical Companies on the Indonesia Stock Exchange. This is done to prove that the existence of a company in the Capital Market in the eyes of investors does not only stop at focusing on achieving high profits as a benchmark for the financial performance of a company's operational activities, but also must be able to provide welfare for shareholders/principals as owners of capital, This indicator is one of the assessments of how far the progress of a company, especially for companies listed on the Indonesia Stock Exchange. This study focuses on the company's performance in generating operating profit and its relationship with the value of the company.The sampling technique used is purposive sampling method where a sample of 6 companies was obtained for the research period 2010-2015. The tests carried out in this study were the classical assumption test (normality test, multicollinearity test, heteroscedasticity test and auto correlation test), analytical method using multiple linear regression analysis with Moderate Regression Analysis model and to test the hypothesis used t test, f test, and determination test.The results of statistical tests show that partially and simultaneously Earnings Aggressiveness and Income Smoothing have a negative effect on the value of pharmaceutical companies on the Indonesia Stock Exchange, Good Corporate Governance cannot be a moderating variable of the effect of Earnings Aggressiveness and Income Smoothing on the value of pharmaceutical companies on the Indonesia Stock Exchange.